Parker solar probe In situ observations of magnetic reconnection exhausts during encounter 1 - Phan,TD; Bale,SD; Eastwood,JP; Lavraud,B; Drake,JF; Oieroset,M; Shay,MA; Pulupa,M; Stevens,M; MacDowall,RJ; Case,AW; Larson,D; et al. (The Astrophysical Journal Supplement, 2020)
Magnetic reconnection in current sheets converts magnetic energy into particle energy. The process may play an important role in the acceleration and heating of the solar wind close to the Sun. Observations from Parker Solar Probe (PSP) provide a new opportunity to study this problem, as it measures the solar wind at unprecedented close distances to the Sun. During the first orbit, PSP encountered a large number of current sheets in the solar wind through perihelion at 35.7 solar radii. We performed a comprehensive survey of these current sheets and found evidence for 21 reconnection exhausts. These exhausts were observed in heliospheric current sheets, coronal mass ejections, and regular solar wind. However, we find that the majority of current sheets encountered around perihelion, where the magnetic field was strongest and plasma β was lowest, were Alfvénic structures associated with bursty radial jets, and these current sheets did not appear to be undergoing local reconnection. We examined conditions around current sheets to address why some current sheets reconnected while others did not. A key difference appears to be the degree of plasma velocity shear across the current sheets: the median velocity shear for the 21 reconnection exhausts was 24% of the Alfvén velocity shear, whereas the median shear across 43 Alfvénic current sheets examined was 71% of the Alfvén velocity shear. This finding could suggest that large, albeit sub-Alfvénic, velocity shears suppress reconnection. An alternative interpretation is that the Alfvénic current sheets are isolated rotational discontinuities that do not undergo local reconnection.